Snowplows on patrol [videorecording (DVD)]. (King George Productions, 2005)
"Kids of all ages will love to watch the heavy equipment in action and learn a few safety tips at the same time. See plows, front end loaders, snowblowers, dump trucks and graders of all sizes, hard at work. Experience a blizzard at an airport, a snowed-in train yard and a baseball stadium full of snow! Visit the snow dump and see mountains of snow, collected from the roads and parking lots! See ice on a river being blown up with explosives to prevent flooding!"--Container.